PENGARUH MOTIVASI DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN OGAN KOMERING ILIR - Choiriyah Choiriyah; Taslim Taslim (Politeknik Negeri Sriwijaya, 2012)
This study aims to determine the significant influence of motivation and working ability to work, either wholly or partially on the working performance of the employees at Education Office Ogan Komering Ilir Regency. Therefore, the analysis used was multiple linear regression analysis. To find out the significant influence of motivation and working ability wholly to the employees working performance the F-test was used, while the significant influence of motivation and working ability partially to employee performance was examined using t-test. Results obtained by multiple regression abalysis with coefficient of determinanation (R2) variable motivation and working ability to the employees performanve was 0,614 (61,4%). While in testing hypotesis, showing that the motivation (X1) and working ability (X2) jointly affect the performance of employees (Y), this is indicated by test results of Fcount Ftable (45,343 at alpha 0,05. While partially, the results of the the t-test motivation (X1) to working performance (Y), obtained tcount t table (13,662 2,021) at alpha 0,05, and working ability (X2) to employee performance (Y), obtained tcount ttable (10,509 2,021) at alpha 0,05. Therefore, it can be concluded that, in this research of motivation variable (X1) and working ability (X2) significantly affected working performance (Y) good on regression testing, as well as in testing the hypothesis.